Urban development with financially sustainable bus transit service : a case study - Chen, Shihui. (2011)
As the urban population grows, the demand for public transport correspondingly increases. It has been proven that high population density is related to high transport usage. This led to urban transport planners planning for more environmental and social sustainable public transit, neglecting the financial sustainability aspect. By improving the financial sustainability of public transit also helps to increase the social and environmental sustainability too.This report sets out to understand the concept of financial sustainability of bus transit service and investigate whether the bus transit service is financially sustainable for the urban development areas. Two urban developments, Serangoon and Hougang planning areas are chosen for investigation due to their close Housing Development Board dwellings percentage. With the current information from SBS Transit Limited and SMRT Buses Ltd, the bus routes, travel time, bus stop distance and headway are determined to find out the fleet size for both areas. Financial analysis will be done to decide whether at the current population density the bus transit service will be financially sustainable. A transportation model is set up to forecast the future trips in the regions. The probability of commuters taking bus is obtained so that the mode choice of commuters is known.